PENGARUH DUKUNGAN SOSIAL KELUARGA TERHADAP SELF-EFFICACY PENYALAHGUNA NAPZA PADA TAHAP RE-ENTRY DI BALAI BESAR REHABILITASI BNN LIDO SUKABUMI - Aliah B Purwakania Hasan (unprimdn.ac.id, 2019)
This study aims to determine whether there is any effect of family support for the self-efficacy of drug users in a large hall rehabilitation BNN Lido Sukabumi and how much influence the social support. The theory used in this study is Albert Bandura's theory that addresses self-efficacy and Friedman's theory that addresses family support. Population and sample used in this study is resident rehabilitated at the stage of re-entry in rehabilitation BNN Lido amounted to 41 people with the use of non-probability sampling that the saturation sampling and questionnaire as a data collection tool. The results were that the requirements of normality with significant value for the variable of social support 0.733 and 0.937 for the variable self-efficacy otherwise normal, social support variable reliability values are 0.8998 and 0.8883 for the variable self-efficacy. The results obtained by using simple linear regression test showed that there is influence of social support for the self-efficacy of drug users, with a significance value of 0.000 (0.000 <than 0.05), meaning that the higher the social support that is given to the maximum will produce good self-efficacy.